Macrophage Polarization and Alveolar Bone Healing Outcome: Despite a Significant M2 Polarizing Effect, VIP and PACAP Treatments Present a Minor Impact in Alveolar Bone Healing in Homeostatic Conditions - Azevedo, Michelle de Campos Soriani; Fonseca, Angélica Cristina; Colavite, Priscila Maria; Melchiades, Jéssica Lima; Tabanez, André Petenuci; Codo, Ana Campos [UNESP]; de Medeiros, Alexandra Ivo [UNESP]; Trombone, Ana Paula Favaro; Garlet, Gustavo Pompermaier (Frontiers, 2021)
Host inflammatory immune response comprises an essential element of the bone healing process, where M2 polarization allegedly contributes to a favorable healing outcome. In this context, immunoregulatory molecules that modulate host response, including macrophage polarization, are considered potential targets for improving bone healing. This study aims to evaluate the role of the immunoregulatory molecules VIP (Vasoactive intestinal peptide) and PACAP (Pituitary adenylate cyclase activating polypeptide), which was previously described to favor the development of the M2 phenotype, in the process of alveolar bone healing in C57Bl/6 (WT) mice. Experimental groups were submitted to tooth extraction and maintained under control conditions or treated with VIP or PACAP were evaluated by microtomographic (µCT), histomorphometric, immunohistochemical, and molecular analysis at 0, 3, 7, and 14 days to quantify tissue healing and host response indicators at the healing site. Gene expression analysis demonstrates the effectiveness of VIP or PACAP in modulating host response, evidenced by the early dominance of an M2-type response, which was paralleled by a significant increase in M2 (CD206+) in treated groups. However, despite the marked effect of M1/M2 balance in the healing sites, the histomorphometric analysis does not reveal an equivalent/corresponding modulation of the healing process. µCT reveals a slight increase in bone matrix volume and the trabecular thickness number in the PACAP group, while histomorphometric analyzes reveal a slight increase in the VIP group, both at a 14-d time-point; despite the increased expression of osteogenic factors, osteoblastic differentiation, activity, and maturation markers in both VIP and PACAP groups. Interestingly, a lower number of VIP and PACAP immunolabeled cells were observed in the treated groups, suggesting a reduction in endogenous production. In conclusion, while both VIP and PACAP treatments presented a significant immunomodulatory effect with potential for increased healing, no major changes were observed in bone healing outcome, suggesting that the signals required for bone healing under homeostatic conditions are already optimal, and additional signals do not improve an already optimal process. Further studies are required to elucidate the role of macrophage polarization in the bone healing process.
Keywords: bone healing; M2 macrophages; osteoimmunology; PACAP; VIP